"Solidarity Is Not a Market Exchange": An RM Interview with Robin D. G. Kelley, Part 2. Issue 2 (3rd April 2019) - Kelley, Robin D. G.; Amariglio, Jack; Wilson, Lucas
Abstract : Part 2 of RM 's interview with historian Robin D. G. Kelley—"Solidarity is Not a Market Exchange"—picks up in detail on Kelley's indebtedness to, and understanding of Cedric Robinson's concept of "racial capitalism." This part of the interview also covers Kelley's use of the Marxian/Hegelian notion of "contradiction;" the intellectual and activist traditions that most influenced Kelley's thinking; Kelley's take on scholars of historical black radical movements in America; Kelley's conceptions of race and racism; his and Robinson's critique of Marx's notion of primitive accumulation and the types of exploitation Marx thought important or not; Kelley's use and criticism of "utopia;" economic and social struggles within universities; Kelley's position on the Althusserian Benin theorist, Paulin Hountandji, and the notions of African "ethnophilosophy" and "unanism;" and Kelley's view of the efficacy, or not, of "diaspora" to describe the condition of black communities in the U.S. and abroad.